Effects of age and gender on reference levels of biomarkers comprising the pediatric Renal Activity Index for Lupus Nephritis (p-RAIL) - Michael R. Bennett; Qing Ma; Jun Ying; Prasad Devarajan; Hermine Brunner (BMC, 2017)
Abstract Background Systemic Lupus Erythematosus (SLE) is a multisystem autoimmune disease that disproportionately effects women and children of minorities. Renal involvement (lupus nephritis, or LN) occurs in up to 80% of children with SLE and is a major determinant of poor prognosis. We have developed a non-invasive pediatric Renal Activity Index for Lupus (p-RAIL) that consists of laboratory measures that reflect histologic LN activity. These markers are neutrophil gelatinase associated lipocalin (NGAL), kidney injury molecule-1 (KIM-1), monocyte chemotactic protein (MCP-1), adiponectin (APN), ceruloplasmin (CP) and hemopexin (HPX). A major gap in the knowledge base and a barrier to clinical utility is how these markers behave in healthy children. We set out to establish a reference range for the p-RAIL markers in a population of healthy children, and to determine if levels of these markers fluctuate with age or gender. Methods Urine was collected from 368 healthy children presenting to Cincinnati Children's primary care clinic for well child visits and assayed for NGAL, KIM-1, MCP-1, APN, CP and HPX using commercially available kits or assay materials. Results Specimens were grouped by age (0-5 years (n = 94); 5-10 (n = 89); 10-15 (n = 93); 15-20 (n = 91)) and gender (M = 184, F = 184). For age and gender comparisons, values were log transformed prior to analysis. The medians (minimums, maximums) of each marker in the combined population were as follows: NGAL 6.65 (0.004, 391.52) ng/ml, KIM-1416.84 (6.22, 2512.43) pg/ml, MCP-1209.36 (9.49, 2237.06) pg/ml, APN 8.05 (0.07, 124.50) ng/ml, CP 465.15 (8.02, 7827.00) ng/ml, HPX 588.70 (6.85, 17,658.40)ng/ml. All p-RAIL biomarkers but adiponectin had weak but significant positive correlations with age, with NGAL being the strongest (r = 0.33, p < 0.001). For gender comparisons, NGAL, CP and HPX were elevated in females vs males (86%, p < 0.0001; 3%, p = 0.007, and 5%, p = 0.0005 elevation of the log transformed mean, respectively). Conclusions We have established a reference range for the p-RAIL biomarkers and have highlighted age and gender differences. This information is essential for rational interpretation of studies and clinical trials utilizing the p-RAIL algorithm.